Ethics of AI Integration in Higher Education: Exploring Moral Dimensions - Sain, Zohaib Hassan; Aziz, Aulia Luqman; Lawal, Uthman Shehu (Journal of Asian Islamic Educational Management (JAIEM), 2024)
In the ever-growing role of artificial intelligence in academic settings, the imperative to address ethical concerns has become paramount. This article delves into a comprehensive analysis of ethical perspectives surrounding AI in higher education, specifically focusing on ensuring equitable access to education, safeguarding student data privacy, and understanding the social implications of teaching automation. The methodological approach involves an extensive review of AI ethics in higher education, supplemented by examining case studies illustrating specific ethical scenarios. The findings highlight the intricate ethical dilemmas associated with AI implementation, revealing tensions between optimising educational processes and preserving equity and autonomy. The research extends to explore the moral obligations of academic institutions, technology developers, and educators engaged in AI integration. The article concludes by emphasising the urgent need for robust ethical frameworks and transparent policies for guiding AI implementation in higher education. This ensures a delicate balance between the advantages of technology and the protection of fundamental moral values.